Assessing CSR of the Business Sector to Energy for all in Nepal - Bista, Raghu Bir (Quest Journal of Management and Social Sciences, 2022)
Background: In Nepal, the existing energy divide with 80 percent off the grid population is extreme, despite the global agenda of energy for all (SDG7). Eradicating this energy barrier to reduce poverty and inequality, SDG 7 advocates renewable energy for an off-the-grid rural population under the CSR fund. Objective: This paper examines the status of the CSR practice of the corporate sector in Nepal and the relationship between the CSR of the corporate sector and renewable energy promotion for energy for all in Nepal to reduce the off-the-grid rural population. Method: This paper employed an explorative research design. Its data sets were primary cum secondary. Result: As a result, the CSR practice of the business sector in a developing country like Nepal is not like as three-pillar principles of CSR. Despite a good amount of profit and knowledge about CSR, the poor, random, and voluntary CSR is a big surprise and a loss of opportunity to create social value across the country. Conclusion: In the future, this corporate sector may be vulnerable to potential social and environmental crises, like the government. Therefore, CSR as an excellent economic instrument to sustain corporate activities and meet society's economic and socio-environmental responsibility is a big hope for renewable energy promotion and development to achieve SDG 7: energy for all by 2030. Originality: This paper is not published anywhere else. Paper Type: Research Paper